PERANAN NAKHODA DALAM MEMOTIVASI SEMANGAT KERJA KRU DI ATAS KAPAL KN. BIMA SAKTI - Firdaus Sitepu (Politeknik Ilmu Pelayaran Semarang, 2018)
The role of the skipper to give motivation to the crew work is urgently needed toprovide impetus in implementing the tasks and jobs on the boat and avoid delay and buildup.The method used in this research is descriptive qualitative. Data were obtained using thetechnique of direct interviews and a questionnaire that is provided to the crew. And to receivedata from the literature related to the title of this research. The conclusion of this study is themotivation of the crew on board was influenced by encouragement from the skipper. And theresult is positive. The crew’s performance is getting better and this is expected to be mainted.